Digital Economic Revolution: The Role of Internet of Things (IoT) And Artificial Intelligence (AI) in Business Management and Accounting - Muhammad Umar A (Oikonomia : Journal of Management Economics and Accounting, 2025)
The digital economic revolution has changed the global business paradigm by integrating Internet of Things (IoT) and Artificial Intelligence (AI) technologies in company operations. IoT enables connectivity between devices that generate real-time data, while AI analyzes the data to improve decision-making. The implementation of these technologies improves operational efficiency, reduces human error, and accelerates business cycles. However, challenges such as data security, unequal access to technology, and the need to improve workforce competencies are still major obstacles. In accounting and business management, AI and IoT have accelerated the digitization of financial records, data analysis, and risk management. AI with machine learning algorithms can detect suspicious financial patterns and improve the accuracy of financial predictions, while IoT supports supply chain efficiency and asset management. However, the adoption of these technologies requires substantial financial investment as well as regulatory and company policy readiness. In addition, challenges in cybersecurity and digital skills gaps demand comprehensive mitigation strategies. Therefore, collaboration between companies, educational institutions and the public sector is crucial in ensuring the success of sustainable and ethical digital transformation. With the right strategy, companies can optimize AI and IoT to increase competitiveness in the digital era